(untitled) (Agora for Physical Education and Sport, 2021)
The paper presents a research on the formation of a critical pedagogical perspective in physical education, sports and recreation in Uruguay. For this, it’s analysed the monthly publications of the Nexo Sport Journal between 1983 and 1990. The analysis identifies three main instances: first, the claim for the pedagogical nature of physical education, one of the main entry point for critical discussions both in a broad and restricted sense. Subsequently, the reception of the Brazilian movement Sports For All is identified as a specific phenomenon that theoretically and ideologically dispute the traditional structures of sports practices. Finally, the recreation emerges as a specific place for questioning the economic-social determinants and the cultural and political conditions of the moment.